Wie rookt gaat sneller dood en betaalt dus meer: Over het belang van oorzaak-gevolg-relaties in verzekeren en de moeilijkheid bij het onderzoeken ervan - Weber, Erik (Ethiek en Maatschappij, 2005)
Smokers die sooner and therefore pay more. On the importance of cause-effect- relations in insurance and the difficulties researching them. For insurers, a correct knowledge of causes are important. An insurance companies who failes to adequatly assess the causes of particular risks will loose its market position due to wrong price setting. In this paper, I discuss possible methods determine the causes of risks, as well as problems and imperfections of those methods.